Optimization of high pressure machine decocting process for Dachengqi Tang using HPLC fingerprints combined with the BoxâBehnken experimental design - Rui-Fang Xie; Zhi-Na Shi; Zhi-Cheng Li; Pei-Pei Chen; Yi-Min Li; Xin Zhou (Elsevier, 2015)
Using Dachengqi Tang (DCQT) as a model, high performance liquid chromatography (HPLC) fingerprints were applied to optimize machine extracting process with the BoxâBehnken experimental design. HPLC fingerprints were carried out to investigate the chemical ingredients of DCQT; synthetic weighing method based on analytic hierarchy process (AHP) and criteria importance through intercriteria correlation (CRITIC) was performed to calculate synthetic scores of fingerprints; using the mark ingredients contents and synthetic scores as indicators, the BoxâBehnken design was carried out to optimize the process parameters of machine decocting process under high pressure for DCQT. Results of optimal process showed that the herb materials were soaked for 45Â min and extracted with 9 folds volume of water in the decocting machine under the temperature of 140Â Â°C till the pressure arrived at 0.25Â MPa; then hot decoction was excreted to soak Dahuang and Mangxiao for 5Â min. Finally, obtained solutions were mixed, filtrated and packed. It concluded that HPLC fingerprints combined with the BoxâBehnken experimental design could be used to optimize extracting process of traditional Chinese medicine (TCM). Keywords: Dachengqi Tang, HPLC fingerprints, BoxâBehnken design, Synthetic weighing method